2019
DOI: 10.1002/hep4.1404
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Cellular Sources and Circulating Levels of Extracellular Vesicles in a Dietary Murine Model of Nonalcoholic Steatohepatitis

Abstract: Circulating extracellular vesicles (EVs) are a novel and emerging biomarker for nonalcoholic steatohepatitis (NASH). It has been demonstrated that total circulating EVs and hepatocyte‐derived EVs are elevated in male mice with diet‐induced NASH. How hepatocyte‐derived EVs change over time and other cellular sources of EVs in NASH have not been determined. Our objective was to define the quantitative evolution of hepatocyte‐derived, macrophage‐derived, neutrophil‐derived, and platelet‐derived EVs in male and fe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
43
0
3

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 45 publications
(48 citation statements)
references
References 53 publications
2
43
0
3
Order By: Relevance
“…In NASH models, circulating EVs also differ in their cell of origin. EVs from adipocytes, macrophages, neutrophils, and platelets are reported to be elevated . Mechanistic studies have demonstrated that both microvesicles and exosomes are released by lipotoxic hepatocytes using distinct cell signaling pathways.…”
Section: Intercellular and Interorgan Crosstalkmentioning
confidence: 99%
See 1 more Smart Citation
“…In NASH models, circulating EVs also differ in their cell of origin. EVs from adipocytes, macrophages, neutrophils, and platelets are reported to be elevated . Mechanistic studies have demonstrated that both microvesicles and exosomes are released by lipotoxic hepatocytes using distinct cell signaling pathways.…”
Section: Intercellular and Interorgan Crosstalkmentioning
confidence: 99%
“…EVs from adipocytes, macrophages, neutrophils, and platelets are reported to be elevated. (104) Mechanistic studies have demonstrated that both microvesicles and exosomes are released by lipotoxic hepatocytes using distinct cell signaling pathways. LPC-stimulated EV release was dependent on mixed lineage kinase 3.…”
Section: Extracellular Vesiclesmentioning
confidence: 99%
“…In the plasma samples of the NASH mice model, there are significant enrichments of EVs derived from different types of cells [45]. In this study [45], the hepatocyte-EVs are enriched as early as at 10 weeks of high-fat feeding compared with the inflammatory EVs derived from the macrophages, and these hepatocyte-EVs are significantly correlated with NASH development. However, due to the limited findings available, the interpretation of these data should be viewed with caution.…”
Section: Extracellular Vesicles (Evs): Adipocyte-derived Evs In Nafldmentioning
confidence: 53%
“…These circulating adipocyte-EVs caused the accumulations of the inflammatory monocytes in the blood and the adipose tissues of the normal mice [44]. In the plasma samples of the NASH mice model, there are significant enrichments of EVs derived from different types of cells [45]. In this study [45], the hepatocyte-EVs are enriched as early as at 10 weeks of high-fat feeding compared with the inflammatory EVs derived from the macrophages, and these hepatocyte-EVs are significantly correlated with NASH development.…”
Section: Extracellular Vesicles (Evs): Adipocyte-derived Evs In Nafldmentioning
confidence: 99%
“…Studies carried out in mouse models of NASH have shown that total circulating EVs and particularly hepatocyte-derived EVs are elevated early in the disease process, while other cell-derived EVs (e.g., macrophage-and neutrophil-derived EVs) appear in the circulation later, likely reflecting the ongoing inflammatory process [65,76]. Proteomic profiling of circulating EVs in experimental NAFLD has been demonstrated to allow differentiation between NAFLD vs. control animals [17].…”
Section: Evs In Nafldmentioning
confidence: 99%